Perceptions of EFL and non-EFL teachers about EFL teacher’s code switching - Miranda Chacón, Cynthia Alexandra (2017)
The following article addresses the topic of code switching among English as a foreign language (EFL) teachers. This article aims to understand the perceptions EFL teachers and non-EFL teachers have toward the frst group’s usage of code switching. Though some similarities about code switching practices were found in both groups, EFL and non-EFL teachers disagree with the functions of code switching and its usage in general. These teachers, from two high schools located in the province of Heredia, provided data which proves similarities about the practice, types and contexts for code switching. Nonetheless, it is noticeable that whereas EFL teachers advocate their language mixing as natural and unconscious, non-EFL teachers claim that EFL teachers are aware enough to know whom, how, when and where to code-switch. This study explores both groups’ perceptions and linguistic attitudes toward such phenomenon. El presente artículo explora el tema y el uso del “code switching”, o mezcla de idiomas, dado entre los docentes de inglés como lengua extranjera (ILE). Dicho artículo pretende comprender las percepciones de los docentes de ILE y de aquellos docentes cuya disciplina o área de trabajo es distinta al inglés hacia el uso del “code switching” por parte de la primera población. Estos profesores, de dos colegios de la provincia de Heredia, brindan información que demuestra similitudes acerca de la práctica, tipos, usos y contextos del “code switching”. No obstante, se destaca que mientras los docentes de inglés defenden que la mezcla de idiomas se da de manera natural e inconsciente, los docentes de otras áreas claman que los docentes de ILE están lo sufcientemente conscientes para saber con quién, cómo, cuándo y dónde hacer uso de mezcla de idiomas. Este estudio explora las distintas percepciones y actitudes lingüísticas de ambas poblaciones acerca de dicho fenómeno.